Relationships between physical activity, physical fitness, somatic fitness, and coordination along childhood and adolescence - João Paulo Saraiva; Luís Paulo Rodrigues (Desafio Singular, 2010)
The two main goals of this review were to understand how the relationships between physical activity, physical fitness, somatic fitness, and coordination are established along the motor development of children and adolescents, and how they would influence their future lives. The web based bibliographic database B-On was searched for peer-reviewed publications during the last decade (2000 to 2009). Search criteria included all articles on relationships between any two of the above named factors. Although different methodological designs and variables were found as markers for the same factor, overall results suggested the existence of a clear positive relationship among physical activity, physical fitness, somatic fitness, and coordination from childhood to adolescence, with a special relevance for the relationship between physical activity and coordination. It was also noted a renewed interest on physical activity and motor coordination developmental characteristics and relationships as well as on their lifelong health effects.